2020
DOI: 10.3390/info11020099
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Social Commerce Intention: An Example of China

Abstract: The rise of social networks is rapidly spreading in China. Using social platforms, individuals are no longer just receivers of Internet information, as consumers generate and share contents with others. Social interaction and spontaneous promotion activities are carried out among consumers, but with the growth of traditional e-commerce slowing down, social commerce derived from social networks is gradually taking shape. Based on Hajli’s theoretical model, this study uses the social support theory and social co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
(24 reference statements)
3
8
0
3
Order By: Relevance
“…This finding can be explained by social support theory and is consistent with prior studies on s-commerce (e.g. Al-Tit et al, 2020;Hajli et al, 2014;Hajli & Sims, 2015;Lee & Chen, 2020;Makmor et al, 2018;Ooi et al, 2018;Riaz et al, 2020;Sheikh et al, 2019;Zhang et al, 2014).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This finding can be explained by social support theory and is consistent with prior studies on s-commerce (e.g. Al-Tit et al, 2020;Hajli et al, 2014;Hajli & Sims, 2015;Lee & Chen, 2020;Makmor et al, 2018;Ooi et al, 2018;Riaz et al, 2020;Sheikh et al, 2019;Zhang et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…The advance and development of web 2.0 applications and information and communication technologies (ICT) has directly contributed to the development of s-commerce (Kim & Park, 2013). S-commerce brings social elements, such as attention, sharing, communication, discussion, and interaction to the e-commerce transaction process (Lee & Chen, 2020). Interactions in the context of s-commerce can also be initiated by consumers that in turn can recommend products/services to other users on s-commerce platforms (Lee & Chen, 2020).…”
Section: S-commercementioning
confidence: 99%
See 2 more Smart Citations
“…This has made social media an important tool in shaping consumer behaviors (Tsai et al, 2012). Previous studies investigated the relationships between social support and social commerce intention (Lee & Chen, 2020;Zhang et al, 2014). Huang et al (Huang et al, 2020) conducted a study on hotel customers and revealed that, by mediation of social media, social support had a significant effect on social commerce intention.…”
Section: Literature Review and Hypotheses Development 21 Social Supportmentioning
confidence: 99%